Shame as a Mediator in the Association Between Emotion Dysregulation and Posttraumatic Stress Disorder Symptom Reductions Among Combat Veterans in a Residential Treatment Program. Issue 1 (22nd July 2021) - Puhalla, Alexander; Flynn, Aidan; Vaught, Amanda
Abstract: Emotion dysregulation (ED) can be defined as one's inability to effectively respond to and manage internal experiences and the expression of emotion. ED has been linked to the development and maintenance of posttraumatic stress disorder (PTSD), with recent research suggesting that reductions in ED may predict improved treatment outcomes among both civilian and veteran populations. However, few studies have examined how changes in ED may predict treatment outcomes among veterans with PTSD and whether certain core features of PTSD, such as shame, may act as potential mediators in the association between ED and PTSD symptom reductions. The present study sought to explore facets of ED, feelings of shame, and PTSD symptoms among 43 combat veterans upon their admission and discharge to a residential PTSD program. The results demonstrated that all variables of interest significantly decreased from admission to discharge, ds = 0.75–1.84. Correlations indicated that reductions in ED, R 2 = .184, and shame, R 2 = .228, were associated with reductions in PTSD symptoms. However, the association between reductions in ED and PTSD was significantly mediated by reductions in shame. Overall, these results suggest that higher levels of emotion regulation may partially affect PTSD symptoms through reductions in shame. This may explain the efficacy of frontline PTSD treatments, as they explicitly focus on the processing of one's traumatic experience by reducing PTSD symptoms through regulation techniques that target emotional–behavioral cycles, which may include the shame–withdraw cycle.